Adhesives and Adhesive Joints in Industry Applications - Rudawska, Anna (IntechOpen, 2019)
This book discusses applications of adhesives and adhesive joints in different branches of industry. The properties of adhesives and adhesive joints, and also the requirements of mechanical properties and chemical and environmental resistance of adhesives and adhesive joints, are very important because proper strength, durability, and time of use are all factors that are dependent on the type of industry. The aim of this book is to present information on the type of adhesives and adhesive joints, in addition to their characteristics, used in different branches of industry. This information should enable scientists, engineers, and designers to acquire knowledge of adhesives and adhesive joints, which could be helpful in selecting the right type of adhesive and adhesive joint to make applications for a particular industry.